Role of Cathepsin G in Rheumatoid Arthritis Diagnosis and Disease Activity Evaluation - Mays Saleh Khamees; Raad Abdulameer Alasady (مجلة الكوفة الطبية)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects 1% of the world's population. It causes chronic inflammation of synovial tissue, leading to joint destruction, poor quality of life, and disability. Cathepsin G (CTSG), which acts as a proteolytic enzyme, can be a factor in RA. These proteases belong to the serine protease family and have a role in autoimmune disorders. They can cause bone and cartilage destruction and an immune response in cases of inflammatory arthritis. The objective of this study is to determine if CTSG could serve as a potential biomarker for the diagnosis and evaluation of the activity of RA. Methods: The study involved 132 patients with inflammatory arthritis, and their serum levels of CTSG and anti-citrullinated peptide antibody (ACPA) were measured using ELISA. Other routine biomarkers, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and rheumatoid factor (RF), were also measured. Results: The mean of CTSG was significantly lower in RA patients (110.53 pg/ml ± 49.959) than in those with other types of inflammatory arthritis (132.65 pg/ml ± 30.199). According to DAS-28 ESR and DAS-28 CRP, the study found no significant difference in CTSG levels across the four disease activity groups (P = 0.585, P = 0.823, respectively). Additionally, CTSG had a significant negative correlation with diabetes mellitus and treatment intake in newly diagnosed RA (P = 0.009, P = 0.041, respectively). This study is the first to evaluate CTSG as an RA diagnostic tool, showing a sensitivity of 70.1% and a specificity of 60.0% at a cut-off value of ≤133.33 pg/ml. Conclusions: The study results suggest that CTSG has potential as a diagnostic biomarker for RA when used alongside other clinical and laboratory criteria. However, it should not be solely relied upon for evaluating RA activity.